Effects of Green Tea (Camellia sinensis) Powder Supplementation on Growth Performance of Broiler Chicken (Research in Agriculture Livestock and Fisheries, 2025)
This study evaluated the impact of dietary green tea (Camellia sinensis) powder supplementation on growth performance and hematological parameters in broiler chickens. A total of 150 Cobb-500 chicks were randomly assigned to three dietary treatments: a control group (T₀; basal diet), an antibiotic-supplemented group (T₁; basal diet + amoxicillin 30% at 1 g/kg feed), and a green tea–supplemented group (T₂; basal diet + 0.5% green tea powder). All birds were reared for 35 days under uniform management conditions. Performance indicators—including body weight gain, feed intake, feed conversion ratio (FCR), dressing percentage, offal weight, intestinal length—and hematological variables (TEC, Hb, PCV, SGOT, and SGPT) were recorded. Broilers receiving green tea exhibited significantly higher (P < 0.001) final body weight (2004.88 ± 6.96 g) and the lowest FCR (1.49), outperforming both the antibiotic (1.54) and control groups (1.61). Hematological profiles also improved markedly (P < 0.001) in the green tea group. Green tea supplementation increased dressing and offal weight percentages without negative effects on bird health. Overall, the findings suggest that inclusion of 0.5% green tea powder in broiler diets enhances growth and physiological status and may serve as a promising natural alternative to antibiotic growth promoters (AGPs).Res. Agric. Livest. Fish. Vol. 12, No. 3, December 2025: 449-454